EKSISTENSI HIMPUNAN LANSIA SAYANG BUNDA DI SULAWESI SELATAN - Amin, Muliaty (Jurnal Dakwah Tabligh, 2018)
The existence of the Elderly Association in South Sulawesi is an organization that concentrates on empowering aumlansia, as a forum for the elderly to stay in touch and contribute to advance South Sulawesi. The research method used is field research, prioritizing da’wah based on the image of Da’i based on research and using science of dakwah communication that synergize with multi disciplinary approach. The implication of this research is the urgency to empower the elderly who are incorporated in the organization of the Association of Elderly Mother of South Sulawesi, whose mission is to empower the elderly. For that, in the future strived to realize the mission of jama’ah for the elderly for empowerment evenly.